Higher-order techniques in computational electromagnetics - Graglia, Roberto D.; Peterson, Andrew F., 1960- (SciTech Publishing, 2015)
The book reviews developments in the following fields: interpolation, approximation, and error in one dimension; scalar interpolation in two and three dimensions; representation of vector fields in two and three dimensions using low-degree polynomials; interpolatory vector bases of arbitrary order; hierarchical bases; the numerical solution of integral and differential equations and an introduction to high-order bases for singular fields.
Keywords: Electromagnetic fields -- Measurement.; Electromagnetic fields -- Mathematics.; elektronické knihy; electronic books